2016
DOI: 10.1080/17470218.2015.1091850
|View full text |Cite
|
Sign up to set email alerts
|

When speech enhances Spatial Musical Association of Response Codes: Joint spatial associations of pitch and timbre in nonmusicians

Abstract: Previous studies have shown that the effect of the Spatial Musical Association of Response Codes (SMARC) depends on various features, such as task conditions (whether pitch height is implicit or explicit), response dimension (horizontal vs. vertical), presence or absence of a reference tone, and former musical training of the participants. In the present study, we investigated the effects of pitch range and timbre: in particular, how timbre (piano vs. vocal) contributes to the horizontal and vertical SMARC eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Two studies in which this was the case used piano and/or vocal sounds as stimuli (Weis et al, 2015;2016). Using sounds with particular timbres (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies in which this was the case used piano and/or vocal sounds as stimuli (Weis et al, 2015;2016). Using sounds with particular timbres (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Cho and colleagues (2012) demonstrated that even non-musicians show a horizontal SMARC effect in a timbre judgement task, but only when a referent tone was presented. Furthermore, Weis et al (2016) showed an influence of both musical timbre and pitch range only in the horizontal space, whereas these variables did not modulate the vertical representation of pitch.…”
Section: Introductionmentioning
confidence: 79%
“…The tendency to represent auditory pitch on space has been consistently reported in various empirical works. A well-known finding supporting the existence of such a spatial mapping of auditory pitch is the Spatial–Musical Association of Response Codes (SMARC) effect (Cho et al, 2012; Lidji et al, 2007; Nishimura & Yokosawa, 2009; Pitteri et al, 2017; Rusconi, 2005; Rusconi et al, 2006; Stewart et al, 2013; Weis et al, 2016), which has been documented along both horizontal and vertical dimensions. In particular, in the vertical space, the SMARC effect refers to the tendency to associate bottom responses with low-pitched tones and top responses with high-pitched tones.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations